2022
DOI: 10.36660/ijcs.20200291
|View full text |Cite
|
Sign up to set email alerts
|

Does a Gluten-free Diet Improve Metabolic Syndrome Parameters? A Systematic Review

Abstract: To review scientific evidence on the effects of a gluten-free diet on body composition and improvement of clinical and biochemical parameters of metabolic syndrome. The Preferred Reporting Items for Systematic Reviews and Meta-Analyzes -PRISMA guidelines were followed. A literature search was performed in the PubMed, ScienceDirect, Trip Database, Bireme and Scielo databases, without language restriction, until March 2021. The terms "gluten-free diet", "obesity", "metabolic syndrome", and "weight loss", and Boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This study used one of the largest data sets in the field to elucidate the relationship between GFD and MS parameters. 6 The study highlighted the lack of effects or evidence of this diet in the general population. Furthermore, the GFD seemed not to promote weight gain, and had controversial effects on MS parameters.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This study used one of the largest data sets in the field to elucidate the relationship between GFD and MS parameters. 6 The study highlighted the lack of effects or evidence of this diet in the general population. Furthermore, the GFD seemed not to promote weight gain, and had controversial effects on MS parameters.…”
mentioning
confidence: 99%
“…The authors also found a lower intake of fiber and a non-significant weight loss in the GFD group compared with controls. 5 The article by Orange et al, 6 in this issue of the Journal is a secondary analysis of data compiled from four studies fulfilling the inclusion criteria for the qualitative synthesis and systematic review. This study used one of the largest data sets in the field to elucidate the relationship between GFD and MS parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation